Frequency of sweet and salty snack consumption among children in relation to their mothers' education level - Mirela Lisičić-Konaković; Senka Mesihović-Dinarević; Elmedin Bajrić; Sanja Jurišić; Ines Musa Trolić; Mladen Ćubela; Zdenko Šarac; Amila Zukanović (Medicinski glasnik, 2023)
Aim: To investigate the frequency of consumption of sweet and salty snacks among children aged 2-18 years in relation to their mothers’ education level. Methods: A descriptive epidemiological study was conducted in five dental practices at the School of Medicine of the University of Mostar from May to October 2022. The data were collected from medical records. Results: Out of a total of 477 children, 172 (36.1%) had mothers with a high school education, while 305 (63.9%) had mothers with a university degree. In the group of preschool children (aged 2-6 years), there were 42 mothers with high school education and 105 with university degree. In the group of school children (age 7-18 years) there were 130 mothers with high school education and 200 with university degree. The difference in the consumption of sweetened beverages among children of mothers with high school and university was not statistically significant. Similar results were found for the consumption of salty snacks, lollipops, caramels and candies. The frequency of the consumption of biscuits, chocolate and cakes (several times a day) was statistically significantly higher among the children of mothers with high school education (p=0.04), especially among school children. Eating habits of children, regardless of the level of education of their mothers, differed significantly only in the consumption of lollipops, caramels, and candies (p=0.03), which were consumed once a day by 79 (63.7%) schoolchildren and 45 (36.3%) of pre-schoolers. Conclusion: A higher level of education among mothers does not necessarily equate to proper nutritional knowledge.
Keywords: child; eating habits; family; snacking